Teacher’s Presence in the Classroom - Asqarova Ziyodaxon Elmurodjon qizi (Journal of Innovation in Education and Social Research, 2023)
The demands of modern education on standardized performance pull us further and further away from a sophisticated and nuanced understanding of what it means to teach. Simple explanations of teaching and learning now run like this: excellent instruction leads to excellent learning, which is correlated with high test scores. Low test scores are a clear indication that poor instruction leads to poor learning. The voices of instructors and students are being marginalized, and we are losing sight of what it means to educate as less time, money, space, and value are allocated to a more complicated idea of education.